Development of the concept for the computational resources management software in the customer service systems - Skulysh, Mariia; Pastrana-Brincones, José Luis; Parhomenko, Dmytro (Igor Sikorsky Kyiv Polytechnic Institute, 2022)
The purpose of the paper is to create a concept of virtual computing space to meet the needs of distributed customer service system, which takes into account the peculiarities of service, the computing node load nature, service quality requirements, and provides energy efficient. Developed models, methods will control the performance of distributed computing infrastructure and flow maintenance processes, reduce downtime of computing resources and provide services to end users at a given level of quality.
Keywords: Servicio al cliente - Innovaciones tecnológicas; Ontologías (Recuperación de la información); Tecnología de la información; Information and communication network; Dynamic resource allocation; Ontology model; Computer system infrastructure; Analysis resources management; QoS